Identification and validation of prognostic biomarkers related to tumor immune invasion in pancreatic cancer - Chen, Minxue; Zhou, Xinyuan; Fan, Yong; Wang, Chen (Frontiers in Genetics, 2025)
BackgroundThe diagnosis and treatment of pancreatic adenocarcinoma (PAAD) remain clinically challenging, and new molecular markers for prognostic assessment and targeted therapy are urgently needed. The tumor microenvironment (TME) and immune invasion play an important role in pancreatic cancer development and progression. Therefore, immunotherapeutic strategies based on the TME and immune invasion may have important clinical value.MethodsIn this study, we extracted transcriptome and clinicopathological data for 179 PAAD samples from the TCGA database and evaluated the immune composition, stromal composition, and infiltrating immune cell landscape in the tumor samples. Then, we identified relevant differentially expressed genes (DEGs) and performed functional annotation and prognostic correlation analysis to identify prognostic biomarkers for pancreatic cancer, the correlation between biomarkers and tumor immune invasion was analyzed to reveal the molecular immune mechanism of pancreatic cancer. Finally, GEO databases (GES71729), GEPIA, TISIDB, TIMER databases and RT-PCR were used for further analysis.ResultsCXCL10 and CXCL11 were highly expressed in pancreatic cancer and associated with poor prognosis of patients through cell adhesion molecules chemokine signaling, cytokine-cytokine receptor interaction, natural killer cell-mediated cytotoxicity, and Toll-like receptor signaling pathways. Finally, the correlation between CXCL10 and CXCL11 and tumor immune invasion was analyzed. The results confirmed that the expression levels of CXCL10 and CXCL11 were positively correlated with the contents of CD8+ T cells. Activated memory CD4+ T cells, M1 macrophages and resting mast cells. The levels of CXCL10 and CXCL11 were related to but negatively correlated with the contents of memory B cells, Tregs and M0 macrophages.ConclusionOur study demonstrates that CXCL10 and CXCL11 are novel biomarkers of TME and immune cell infiltration in pancreatic cancer by affecting the distribution of immune cells. CXCL10 and CXCL11 may be new targets for molecular targeted therapy and immunotherapy of pancreatic cancer.